Design of C-band 9 MeV Small Focus Standing Wave Electron Linear Accelerating Structure - LI Shilin, YANG Jinghe, FAN Yuxuan, WANG Bo, YANG Yu, LEI Han (Yuanzineng kexue jishu, 2025)
With the development of microwave technology, accelerators have become an indispensable part of scientific research and daily applications gradually, it has been used in many fields, such as medical radiotherapy, radiation sterilization, industrial machinery flaw detection and so on. High-energy CT is one of the most significant and effective methods in the field of nondestructive testing, however, its accuracy is decisively affected by the size of the focus produced by the electron accelerator. To obtain a small electron beam spot at the target, there are two ways: one is to add focusing units downstream the beam outlet of the existing accelerator to compress the transverse size of the beam and draw out the beam, but with this method, the energy spread of the accelerating tube will be too large to bunch effectively; the other is to study the increase of the emittance of the electron beam emitted from the electron gun in the accelerator motion by calculating the transverse dynamics of the electron beam when design the accelerator, and then, by discussing how to control the movement of beam in the electron linac, the electron beam with the smallest size can be obtained, and appropriate measures can be taken to obtain small beam spots and ray doses that meet the requirements of nondestructive testing. At present, there are two mainstream accelerating structures on the market: traveling wave accelerating structure and standing wave accelerating structure. Compared with traveling wave accelerating structure, standing wave accelerating structure has the advantages of high accelerating gradient, stable operation and compact structure, so it is more suitable to be used in the field of nondestructive testing. In order to meet the needs of high-performance accelerators for high-resolution nondestructive testing, a C-band small focus standing wave electron linear accelerating structure was designed in this paper. The physical design of the accelerating structure was carried out by the combination of RF phase focusing method and electrostatic focusing method, the beam dynamics simulation design was carried out by Superfish and Parmela, and then the whole tube cavity chain was determined by equivalent circuit analysis and CST electromagnetic field simulation. The accelerating structure consists of 3 bunching cavity units and 19 accelerating cavity units with a total length of about 548 mm. The frequency of the accelerating structure is 5 710 MHz, the beam energy is 9.11 MeV, the target’s full width at half maximum (FWHM) is about 0.45 mm, and the capture efficiency is about 35.8%.